Impact of microfinance on rural smallholder farmers in MT. Darwin District of Mashonaland Central Povince in Zimbabwe : a case of Fachig Trust - Choga, Joseph (University of Limpopo (Turfloop Campus), 2013)
Rural areas of Zimbabwe suffered acute shortage of banking services. Conventional banks feared high transaction costs and lack of collateral associated with this market segment. This research aimed at evaluating impact of microfinance on rural farming sector. Finding out the general banking and microfinance situation, appraising scheme impact and making recommendations were the research’s objectives. A descriptive research design was used. A population of 3,400 members constituting 289 Investment Groups (IGs) was used. Quota and purposive sampling were used to select 20 IGs and 154 individual respondents. Sample survey, Focus Group Discussions (FGD) and Key Informant Interviews (KII) were data collection methods. The survey findings showed that the five Department For International Development’s (DFID’s) Sustainable Livelihoods Approach (SLA) asset bases increased more for the treatment than the control groups, signifying microfinance impact. Wealth ranking, meant to triangulate survey results, depicted upward mobility of groups; old ones transcending to rich categories while the new moved into top poor rank, also demonstrating impact. Further, scheme achieved women empowerment basing on their numerical predominance and improved self-confidence, signifying impact. The study recommends that Farmers’ Association of Community self-Help Investment Groups (FACHIG) resuscitated its savings component using the Self-Help Group (SHG) thrift approach to ensure scheme sustainability. In addition, climate change, a phenomenon which increased droughts, could have dampened impact. However, the research did not delve into this area, compelling a future study.
Thesis (LLM. (Management and Law)) -- University of Limpopo, 2013
Keywords: Banking services; Zimbabwe; Microfinance; Rural smallholder farmers; 338.9006891; Microfinance -- Zimbabwe; Rural development -- Zimbabwe; Farms, Small; Business enterprises -- Zimbabwe -- Finance